The state of cardiac surgery in EthiopiaCentral MessagePerspective - Salem Argaw, MD, MPH; Abraham Genetu, MD; Dominique Vervoort, MD, MPH, MBA; Fekede D. Agwar, MD (JTCVS Open, 2023)
Objectives: Six billion people globally do not have access to cardiac surgical care. In this study, we aimed to describe state of cardiac surgery in Ethiopia. Methods: Data on status of local cardiac surgery collected from surgeons and cardiac centers. Medical travel agents were interviewed about number of cardiac patients who were assisted to travel abroad for surgery. Historical data and number of patients treated by non-governmental organizations were collected via interviews and by accessing existing databases. Results: Patients access cardiac care via 3 avenues: mission-based, abroad referral, and care at local centers. Traditionally, the first 2 have been the main mode of access; however, since 2017, an entirely local team has begun performing heart surgery in the country. Currently, surgical cardiac care is provided at 4 local centers: a charity organization, a tertiary public hospital, and 2 for-profit centers. Procedures at the charity center are provided for free, whereas in others, patients mostly pay out of pocket. There are only 5 cardiac surgeons for 120 million people. More than 15,000 patients are on waitlist for surgery, mainly because of lack of consumables and limited numbers of centers and workforce. Conclusions: There is a change in the trend from non-governmental mission- and referral-based care toward care in local centers in Ethiopia. The local cardiac surgery workforce is growing but still insufficient. The number of procedures is limited with long wait lists due to limited workforce, infrastructure, and resources. All stakeholders should work on training more workforce, providing consumables, and creating feasible financing schemes.